2020
DOI: 10.3382/ps/pez495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on the relationship between metabolizable energy and digestible energy for broiler chickens

Abstract: A total of 960 male Ross 308 chicks (day-old) were used to investigate the effect of age on the relationship between metabolizable energy (ME) and digestible energy (DE) for broiler chickens. Bird growth variables, nitrogen retention (NR), nitrogen digestibility (ND), as well as the relative weight of liver, pancreas, and the gastrointestinal tract were determined. Practical diets that compared 2 cereals (corn and wheat) and exogenous xylanase (0 or 16,000 BXU/kg) were evaluated at 5 ages (7, 14, 21, 28, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 38 publications
6
39
3
1
Order By: Relevance
“…The current findings disagree with the widely assumed perception that energy utilization increases with age ( Tancharoenrat et al, 2013 ; Yang et al, 2020 ). The absence of positive effect of advancing age on the AMEn of all grains in the current study was also confirmed by the lack of positive effects on DM and N retention.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current findings disagree with the widely assumed perception that energy utilization increases with age ( Tancharoenrat et al, 2013 ; Yang et al, 2020 ). The absence of positive effect of advancing age on the AMEn of all grains in the current study was also confirmed by the lack of positive effects on DM and N retention.…”
Section: Discussioncontrasting
confidence: 99%
“…All previous studies on age-related responses have been conducted with grain-based complete diets ( Olukosi and Bedford, 2019 ; Yang et al, 2020 ). To our knowledge, no published data are available on age effects for the AMEn of individual cereal grains.…”
Section: Introductionmentioning
confidence: 99%
“…Although the focus of the present work is TIDE, a discussion of AIDE data is relevant, and pertinent comparisons are included because the limited published data available on ileal digestible energy to date relate to AIDE. Most data are for the AIDE of complete diets ( Camden et al., 2001 ; de Coca-Sinova et al., 2008 ; Romero et al., 2014 ; Yang et al., 2020 ), but some studies have also reported the AIDE of individual cereal grains, including corn ( Gehring et al., 2012 ), wheat, and barley ( Scott et al., 1998 ). In the present study, the AIDE of corn, sorghum, wheat, and barley was determined to be 3,544, 3,296, 2,758, and 2,519 kcal/kg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of the metabolizable energy of feed ingredients before 14 days of age may present lower values than those obtained with older birds, and the metabolizable energy values determined in older broilers may overestimate the availability of energy for younger birds. (27) Sakomura et al (28) found a linear increase in the activity of amylase, trypsin, and lipase with the advancing age of broilers (1 to 7, 8 to 14, 15 to 21, and 22 to 28 days), and the phase of the highest increase occurred between the first and second weeks of age, coinciding with the maximum allometric growth of pancreas.…”
Section: Resultsmentioning
confidence: 98%